Investigation of mixture formation in a diesel spray by tracer-based laser-induced fluorescence using 1-methylnaphthalene - Lind, Susanne; Retzer, Ulrich; Will, Stefan; Zigan, Lars (Proceedings of the Combustion Institute, 2017)
The paper presents a proof-of-principle study for the simultaneous imaging of temperature and fuel partial density in a realistic diesel spray using tracer-based planar laser-induced fluorescence (Tracer-PLIF). The fluorescence of 1-methylnaphthalene (1-MN) is characterized in a flow cell with respect to temperature and pressure in nitrogen atmosphere at IC engine conditions with excitation at 266nm. The strong spectral red-shift of 1-MN with increasing temperature is used for two-color-LIF. The fuel partial density is determined with only one detection channel. This technique is further applied for investigation of temperature and fuel partial density in a diesel spray studied at 5MPa and 800K in an injection chamber. Averaged images are presented for a pilot injection revealing a maximum temperature difference between fuel jet and ambience of about 150K with a maximum fuel partial density of about 220g/m. Between 1300 and 1700μs after visible start of injection, the mixing temperature increases by up to 50K and the fuel partial density decreases by about 20g/m because of gas entrainment. The suitability of the LIF technique for single-shot measurements is further demonstrated by studying the cyclic spray variations, which allows for a detailed understanding of mixture formation in IC engine combustion. This enhanced tracer-based LIF-technique for the first time allows for a simultaneous quantification of temperature and fuel partial density at elevated temperatures, which are highly relevant for diesel engine
Keywords: 1-methylnaphthalene; Diesel spray; Fuel partial density; Laser-induced fluorescence; Temperature